2020
DOI: 10.1124/dmd.120.000011
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bile Acid Profile of Newborns Born by Cesarean Section Is Characterized by Oxidative Metabolism of Primary Bile Acids: Limited Roles of Fetal-Specific CYP3A7 in Cholate Oxidations

Abstract: This work aims to investigate how the bile acid metabolism of newborns differs from that of adults along the axis of primary, secondary, and tertiary bile acids (BAs). The total unconjugated BA profiles were quantitatively determined by enzyme digestion techniques in urine of 21 newborns born by cesarean section, 29 healthy parturient women, 30 healthy males, and 28 healthy nonpregnant females. As expected, because of a lack of developed gut microbiota, newborns exhibited poor metabolism of secondary BAs. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Most recently, we reported that human newborns show a BA metabolism pattern predominated by primary BA oxidations due to immaturity of the secondary BA metabolism . As far as we know, the RFP induced compensatory transition of the BA metabolism from the fecal disposition of secondary BAs to the urinary excretion of primary BAs in dogs looks intriguingly like the BA metabolism pattern of newborns.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Most recently, we reported that human newborns show a BA metabolism pattern predominated by primary BA oxidations due to immaturity of the secondary BA metabolism . As far as we know, the RFP induced compensatory transition of the BA metabolism from the fecal disposition of secondary BAs to the urinary excretion of primary BAs in dogs looks intriguingly like the BA metabolism pattern of newborns.…”
Section: Discussionmentioning
confidence: 86%
“…Most recently, we reported that human newborns show a BA metabolism pattern predominated by primary BA oxidations due to immaturity of the secondary BA metabolism. 58 As far as we know, the RFP induced compensatory transition of the BA metabolism from the fecal disposition of secondary BAs to the urinary excretion of primary BAs in dogs looks intriguingly like the BA metabolism pattern of newborns. Because newborns have a specific pathway of primary BA oxidation to produce the fetal-specific tetrahydroxy-cholan-24-oic acids (Tetra-BAs), we investigated the raw data to clarify whether Tetra-BAs were also elevated in dogs by RFP treatments.…”
Section: ■ Discussionmentioning
confidence: 96%
“…[36][37][38] An atopic immune response increases the risk of JIA when exposure to fetal microorganisms is interfered with. 39 Maternal smoking of more than 20 cigarettes per day and smoking during pregnancy were found to be associated with a reduced risk of JIA in meta-analyses. Prenatal smoking is generally associated with poor offspring health.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…In humans, the bile acid profiles of newborn infants (infants less than 48 h old) were largely composed of primary bile acids and were markedly different from adult bile acid profiles (Wang et al 2020b). In mice and rats, the gut microbiota and bile acid pool both diversify rapidly after birth.…”
Section: Sex Differences and Bile Acidsmentioning
confidence: 99%
“…Since mice show the opposite pattern, this difference is important to consider when using mice as a model for the effects of bile acids on physiology. While there are consistent sex differences in the total bile acid pool in humans, the reported sex differences in terms of the types of primary and secondary acids vary among studies (Fisher & Yousef 1973, Bennion et al 1978, Wang et al 2020b). In addition, little is known about how age interacts with sex differences in primary and secondary bile R67 Reproduction (2023) 165 R61-R74 acid metabolism although one study indicated that sex steroids, which change in concentration throughout the lifespan, may indirectly affect secondary bile acid metabolism (Ridlon et al 2010).…”
Section: Sex Differences and Bile Acidsmentioning
confidence: 99%